The effect of swidden agriculture on ant communities in Madagascar. (January 2022) - Finch, Elizabeth A.; Rajoelison, Eric T.; Hamer, Matthew T.; Caruso, Tancredi; Farnsworth, Keith D.; Fisher, Brian L.; Cameron, Alison
Abstract: Swidden agriculture is a widespread subsistence farming method in the tropics, which is being intensified as human populations grow. This study is the first to investigate the impacts of land degradation from swidden upon ant species (both native and introduced) across the full degradation gradient, from forest, to tree fallows, to shrub fallows, to exhausted land. Ant communities in closed canopy forests had higher species diversity and were taxonomically distinct, but as land became increasingly degraded, a significant reduction in overall and native species richness was detected, as were changes in overall community composition. Whilst native species decreased across the degradation gradient, introduced species increased. There was also a significant correlation in community compositional changes between native and introduced species which was independent from environmental factors. Co-occurrence analysis, however, suggested there was little evidence that introduced species were significantly impacting the communities of native species. This suggests these patterns are both separately driven by habitat degradation. Degraded fallow habitats were found to harbour unique and endemic species, including 22.4% of the species found in closed canopy forest. Together, our results highlight the potentially detrimental effects of further spread and increased intensification of swidden systems in tropical ecosystems. The conservation of existing closed canopy forests is of utmost importance but we also highlight that the fauna of degraded swidden habitats could still be important for biodiversity conservation in agricultural landscapes across the tropics. Highlights: Ant communities in forests were species rich and compositionally unique. Increased degradation led to species richness declines and composition changes. Increased degradation also increased the prevalence of introduced ant species. Degraded habitats are not devoid of species and could play a role for conservation.